2013
DOI: 10.1097/mph.0b013e31829eec33
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring in Pediatric Oncology

Abstract: A formal Mentorship Program within the Children’s Oncology Group (COG) was established to pair young investigators (mentees) with established COG members (mentors). Despite the AAP policy statement promoting mentorship programs, there are no publications describing and evaluating national mentorship programs in pediatric subspecialties. In this study, a series of internal program evaluations were performed using surveys of both mentors and mentees. Responses were de-identified and analyzed to determine the uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…One novel aspect of our mentoring program is the mentees’ ability to self-select their mentors from an Internet-based profile list of registered mentors on the ASPHO Web site, representing many subspecialties within the field of PHO, which is not limited to oncology but also includes nonmalignant hematology and stem cell transplant. 23 A recent systematic review reported that most mentees preferred to identify their own mentors, supporting our novel approach. 13 In order to initiate customized individual development plans with their mentors, mentees were also able to define their goals and their needs for personal and professional development.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…One novel aspect of our mentoring program is the mentees’ ability to self-select their mentors from an Internet-based profile list of registered mentors on the ASPHO Web site, representing many subspecialties within the field of PHO, which is not limited to oncology but also includes nonmalignant hematology and stem cell transplant. 23 A recent systematic review reported that most mentees preferred to identify their own mentors, supporting our novel approach. 13 In order to initiate customized individual development plans with their mentors, mentees were also able to define their goals and their needs for personal and professional development.…”
Section: Discussionmentioning
confidence: 59%
“…Although other mentoring models exist, 3,13,22 including within pediatric oncology (sponsored by the COG), 23 the ASPHO mentoring program offers unique features and was not meant to compete with existing mentorship programs. One novel aspect of our mentoring program is the mentees’ ability to self-select their mentors from an Internet-based profile list of registered mentors on the ASPHO Web site, representing many subspecialties within the field of PHO, which is not limited to oncology but also includes nonmalignant hematology and stem cell transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Some have published data showing increases in both participant satisfaction and self-reported productivity with participation in such a program (5). A case-control study showed gynecologic oncology faculty and fellows from more productive institutions were not only more likely to have a research mentor, but also were more likely to have a formal program in place at their institution that connects mentors and mentees (2).…”
Section: Discussionmentioning
confidence: 99%
“…A successful career in academic medicine, though firmly rooted in personal drive, dedication and hard work, also requires input and advice from those more seasoned and experienced. Mentorship is often cited as a key component of successful academic career development, and has been studied in several disciplines of medicine (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Though several nuanced definitions of a mentor exist, a mentor is most often described as an experienced and trusted advisor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation